(untitled) (Economics and region, 2020)
The effectiveness of education funding in Ukraine in general and vocational education and training in particular is analyzed in the study. It is proved that Ukraine has disparities between market needs in certain specialties and the number of graduates. The needs in blue collar workers have resulted in the decline in vocational schools number and their graduates. According to the analysis of the structure and sources of education and VET financing in Ukraine, it has been proved, that positive results of education decentralization and educational services financing can be assured by raising additional resources. It has been shown that additional income to finance vocational education and training is available to local budgets through the investment of temporarily free funds in deposit accounts and application of stock market instruments. The proposed mechanisms are efficient if they are used in the process of local councils’ financial resource management in the short and long term.